2020
DOI: 10.1038/s41416-020-0733-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of 5-year relapse-free survival in HR+/HER2- breast cancer patients treated with neoadjuvant endocrine therapy: pooled analysis of two phase 2 trials

Abstract: Background Few data are available on survival and predictive factors in early breast cancer (BC) patients treated with neoadjuvant endocrine therapy (NET). Methods This is a pooled analysis of two multicentre, randomised non-comparative phase 2 clinical trials evaluating neoadjuvant anastrozole and fulvestrant efficacy for postmenopausal HR+/HER2- breast cancer patients: HORGEN (NCT00871858) and CARMINA02 (NCT00629616) studies. Results In tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 27 publications
1
23
0
1
Order By: Relevance
“…Reduction in Ki67 >40% between pretreatment and 10–14 days was related to pathological responses. A pooled analysis of two multicenter, randomized, noncomparative, phase 2 clinical trials (HORGEN and CARMINA02) evaluating neoadjuvant anastrozole and fulvestrant efficacy for postmenopausal HR+/HER2- breast cancer indicated that PEPI can identify a subset of patients with poorer prognosis who should be offered all appropriate adjuvant therapy ( 55 ). Ki67 in neoadjuvant trials predicted the long-term outcomes of large adjuvant trials; Ki67 and PEPI can be predictors for evaluating the recurrence-free survival of breast cancer patients with NET ( 50 ).…”
Section: Ki67 In Neoadjuvant Endocrine Therapymentioning
confidence: 99%
“…Reduction in Ki67 >40% between pretreatment and 10–14 days was related to pathological responses. A pooled analysis of two multicenter, randomized, noncomparative, phase 2 clinical trials (HORGEN and CARMINA02) evaluating neoadjuvant anastrozole and fulvestrant efficacy for postmenopausal HR+/HER2- breast cancer indicated that PEPI can identify a subset of patients with poorer prognosis who should be offered all appropriate adjuvant therapy ( 55 ). Ki67 in neoadjuvant trials predicted the long-term outcomes of large adjuvant trials; Ki67 and PEPI can be predictors for evaluating the recurrence-free survival of breast cancer patients with NET ( 50 ).…”
Section: Ki67 In Neoadjuvant Endocrine Therapymentioning
confidence: 99%
“…The NEWEST trial compared 16 weeks of neoadjuvant fulvestrant at doses of 250 to 500 mg. Tumor response rates at week 16 were similar between the two dosages (22.9 and 20.6%, respectively) [ 17 ]. We recently published a pooled analysis of two sister phase II trials evaluating anastrozole and fulvestrant as NET in postmenopausal HR+/HER2- breast cancer patients (CARMINA02 and HORGEN trials) [ 18 , 19 , 20 ]. These two trials had a similar design and included similar populations and the primary endpoint in both studies was clinical response rate at 6 months.…”
Section: Endocrine Agentsmentioning
confidence: 99%
“…In our pooled analysis of the CARMINA02 and HORGEN trials, we used the Sataloff classification to assess the pathological response rate and its prognostic value after NET [ 18 ]. Somewhat similar to the RCB score, the Sataloff classification examines the therapeutic effect of neoadjuvant therapy by measuring the reduction in tumor cell number in breast and nodes [ 48 ].…”
Section: Assessing Response To Netmentioning
confidence: 99%
See 2 more Smart Citations